The role of Health Education in Improving Community Competence in Environmental Health Management - Hutapea, Lyna M. N.; Hutapea, Dwight Mahaputera Marulitua (Journal of Public Health Indonesian, 2024)
This study aims to explore the role of health education in improving community competence in Environmental Health Management. This study uses a qualitative approach with the method of case studies conducted in several communities that have undergone environmental health education programs. Data were collected through in-depth interviews with participants, health educators, and direct observation of activities carried out by the community. The results showed that health education plays a significant role in improving public understanding of the importance of environmental health, such as waste management, sanitation, and hygiene maintenance. This educational Program not only increases knowledge, but also influences changes in people's behavior in maintaining a healthy environment. In addition, public awareness of the importance of active participation in Environmental Health Management has also increased. This study confirms that proper health education can strengthen the competence of communities in managing environmental health, and suggests the need to implement sustainable programs based on local needs.